PEMURNIAN PROTEASE DARI BUAH DAN DAUN MENGKUDU (Morinda citrifolia L.) [Purification of Proteases from Fruits and Leaves of Noni (Morinda citrifolia L.)] - Dwi Ishartani; . Elfi; Nuri Andarwulan; Dahrul Syah (Jurnal Teknologi dan Industri Pangan, 2011)
Proteases have been widely used in cancer treatment, wounds healing, overcoming digestion disorder and other modern pharmaceutical applications. Proteases may be present in fruits and leaves of noni (Morinda citrifolia L.) since the plant has been used traditionally in wound healing. This research aimed to purify proteases from noni’s fruits and leaves at two maturity stages, i.e. fruits with green-yellow (TK2) and white-yellow (TK4) skin colour, also leaves from shoot and base. Proteases were purified through several steps consisting of extraction, precipitation using saturated ammonium sulfate and dialysis followed by electrophoresis under denaturing conditions (SDS-PAGE) and zymography. The specific activity of the four extracts showed different trend during purification. The specific activity of TK2 fruit, shoot and base leaves decreased whereas TK4 fruits increased. TK2 crude extract had a higher specific activity (3.79 U/mg) than the other crude extracts. SDS-PAGE and zymogram using 12% acrylamide indicated that the dialysates were not pure proteases. The molecular weight profiles of the TK2 dialysates were similar to TK4 dialysates, while those of shoot leaves dialysates were similar to the base leaves dialysates. The SDS-PAGE separated the enzymes in the fruit dialysates into several bands of polypeptides,i.e. 24-26kDa, 14-15kDa, 12-13kDa and the smaller ones, and also separated the enzymes in the dialysates of leaves into two bands, 70kDa and 58-61.5kDa. Protease bands detected in the zymogram of fruits were estimated at ~25kDa, ~27kDa, and 37-38kDa, whereas of those of leaves were estimated at ~29kDa and ~50kDa. The ~25kDa and ~29kDa protein bands appearing in zymogram were similar to papain’s and bromelain’s molecular weight.